Religiositas Pada Seni Kontemporer Berbasis Augmented Reality Karya Nina Chanel Abney Berjudul “Imaginary Friend” - AHMAD SAHAR SYAMSUDIN (Institut Seni Indonesia Yogyakarta, 2022)
The development of art and design as well as technology has grown rapidly, all three have changed the influence of each other. So that contemporary art and design has emerged with a variety of uniqueness. These changes cannot be separated from culture and religiosity as well as the life of the creator. This article is intended to analyze the value of religiosity in the work of artist Nina Chanel Abney entitled “Imaginary Friend”. This article uses a descriptive qualitative method. The results of the analysis show that Nina Chanel Abney's artwork uses Augmented Reality technology as the basis for the embodiment of the work. It is also known that there are signs of elements of Christian religious religiosity. In addition, there appears to be a hidden element of the Pan-Africanism movement.